The philosophy of sustainable development and the implementation of its postulates in social practice - Hull, Zbigniew (Studia Ecologiae et Bioethicae, 2019)
The deepening global ecological crisis raises a question about the practical effectiveness of postulates formulated based on the philosophy of sustainable development. In attempting to answer this question, I assumed that the philosophy of sustainable development is a political philosophy, which functions in the sphere of socio-economic life as a fashionable/binding ideology, approved and postulated by the currently dominating political forces and large companies. When I confronted, on the scale of globalised world, the slogans and declarations with political practice and the functioning of the world economy, I came to the conclusion that the current efforts to implement the idea of sustainable development have only slightly contributed to reducing the threat of a global ecological disaster. In fact, they are a kind of ‘smoke screen’ for business and politicians, who in practice continue the existing course of civilisational development aimed at continuous growth of consumption and GDP. This shows that the philosophy of sustainable development is already practically ineffective and is today not able to cope theoretically with the challenges facing humanity in the 21st century.